Digital business strategy of enterprise and its components - Liubov Lipych (Економічний форум)
Technological changes affect the management of the enterprise, forcing to make decisions regarding the choice of development strategy. It has been established that the large-scale digital transformation of companies requires the transformation of a functional IT strategy into a digital business strategy. It is substantiated that the digital business strategy assumes that the organization formulates and implements its strategy on the basis of digital resources that create added value for it, enable it to compete in the market and form new standards and business models. This means: going beyond traditional thinking about IT strategy, going beyond systems and technologies, basing the company's activities on a resource-oriented approach and intangible resources, connecting digital strategy with business value creation and operational efficiency. It is proven that the digital business strategy describes the overall vision of the company in the context of digitalization, including strategic measures to achieve it. It defines specific, short-, medium- and long-term digitalization goals and initiatives in the context of products, services and value creation, as well as the company's organization and culture. A digital business strategy includes four elements: scope, scale, velocity, and sources of value. Analysis of the sphere of influence of the digital business strategy shows that it goes beyond traditional functions and business processes, includes the digitization of products and services and related information, expands the scope of the organization and its existing functions, goes beyond it and transforms the supply chain into a dynamic ecosystem. The digital world is characterized by the following ways of increasing the effect of scale: the ability to dynamically and flexibly change, network effects from the use of multi-vector digital platforms, the use of diverse, distributed information from different sources, participation in alliances and partner programs. Speed in the context of digital strategy can be considered in four dimensions: the speed of product introduction, the speed of decision-making, the speed of coordination and regulation of the supply chain, the speed of forming a network of relationships and its adaptation. Digital strategy creates additional dimensions that change the way value is created. These include: use of various information, use of multi-vector business models, coordination of models in networks, control of network architecture